Instructional Design of Online Training for ECE Educators: A Project-Based and Andragogical Approach - Tepati Kewajiban; Susy Puspitasari; Suryo Prabowo; Ahmad Syaikhu; Apri Kasman (Indonesian Scientific Journal, 2025)
Enhancing Early Childhood Education (ECE) educators' digital media creation skills is crucial for innovative teaching, yet effective, practical professional development often remains a significant challenge. This article presents a detailed instructional design for an online training program, developed as an outcome of a community service initiative with a private ECE institution in Indonesia. This initiative involved its eleven educators, who possessed varied initial digital competencies, and aimed to address their specific needs. The design process employed a systematic needs analysis, integrating project-based learning and established andragogical principles to ensure relevance and practical application for adult learners. The resulting online program features a three-tiered competency structure (Beginner, Intermediate, Advanced), where each level culminates in authentic media creation projects, fostering skills through learner-centered, reflective, and collaborative activities. This theoretically-grounded instructional design offers an adaptable model anticipated to significantly improve ECE educators' digital competencies and creative capacities, thereby enriching children’s learning experiences.